Sorption isotherms for oat flakes (avena sativa) (2014)
Moisture sorption isotherms of oat flakes were determined at temperatures of 5, 25 and 37ºC, using a gravimetric technique in an aw range of between 0.107 and 0.855. These curves were modeled using six equations commonly applied in food. The quality of the fit was assessed with the regression coefficient (r2) and the mean relative percentage error (MRPE). The best fit were obtained with the Caurie model with r2 of 0.996, 0.901 and 0.870, and MRPE of 7.190, 17.878 and 16.206, at 5, 25 and 37ºC, respectively. The equilibrium moisture presented a dependence on temperature in the studied aw range, as did the security moisture (XS). These results suggest that the recommended storage conditions of oat flakes include: a relative air humidity of 50% between 5 and 251ºC and of 38% up to 37ºC.